The Problem of the Obligatory Military Service in Colombia and the Right to Conscientious Objection - Rodríguez-Páez, Nicolás (Universidad Pedagógica y Tecnológica de Colombia, 2016)
The conscription is an institution that was legalized in 1993 with law 48, but that responds to the dynamics of recruitment that the army makes since the birth of Colombia as a Nation-State. Being a naturalized practice, it is not questioned the affectation that brings over the Colombian youths, who are forced to fulfill a duty that often goes against their conscience. For these cases, the Constitutional Court declare the right to conscientious objection as a fundamental right, and in different pronouncements has delimited its scope,delimitation that, sometimes, is detrimental to the guarantee of rights of the young person. This article intends to problematize conscription, as well as to review the Court’s judgments on the subject, with the intention of showing its progress and problematic points, in order to guarantee the rights of young people who for reasons of conscience refuse to Military service.